Analysis of Education and Communication Strategies in Increasing Understanding and Public Awareness of Insurance at Panin Dai-Ichi Life Company - Fadhilah, Putri; Prastyaningtyas, Efa Wahyu (Universitas Nusantara PGRI Kediri, 2025)
Research Aim : The purpose of writing this article is to further examine marketing strategies and educational approaches that can increase public awareness of the importance of insurance. Design/Methods/Approach : The author conducted research through a qualitative approach to explore the education and communication strategies implemented by Pani Dai-Ichi Life, Data collection was carried out in three ways namely; observation, interviews, and documentation. Research Findings : The education and communication strategy implemented by Panin dai-Ichi Life has proven effective in expanding access to information and increasing public awareness about the importance of insurance, especially among the younger generation. The educational approach is carried out through workshop activities in Surabaya area campuses, as well as informative content on social media that discusses financial management, financial protection, and risk management. Theoretical contribution/Originality: Academic basis that can be utilized to design more efficient education and communication strategies in increasing public understanding and awareness of insurance. Practice/Policy Implications: 1. optimization of digital education through webinars, and social media, 2. Interactive communication strategies such as question and answer sessions and insurance benefit simulations, 3. Use of simple lenguage to make information easier to understand. Research limitations: This study has limitations such as a regional focus that only covers Surabaya, so the findings may be less representative of other regional contexts.